Determinants of Hospital Employee Performance: The Role of Motivation and Organizational Dynamics - Wati, Wiwin Sri Niscahya; Bumi, Candra; Wijaya, Dodi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Employee performance in hospitals has become a strategic concern amid increasing service demands, high workload, and declining public satisfaction. These challenges underscore the importance of empirically identifying the key determinants of employee performance to support evidence-based managerial interventions. Understanding how organizational and motivational factors influence performance is essential for strengthening hospital service quality and institutional sustainability. This study aimed to analyze the effects of competency development, leadership style, work facilities, and work motivation on employee performance at hospital. A quantitative study with a cross-sectional design was conducted. Data were collected from 210 hospital employees using a stratified random sampling technique to ensure proportional representation across work units. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and total effects among variables within the proposed structural model. The analysis revealed that leadership style was the most dominant determinant of employee performance, with a total effect value of 0.497 (p = 0.000). Competency development emerged as the second strongest determinant, with a total effect of 0.338 (p = 0.000). Work motivation also had a statistically significant contribution to employee performance, with a total effect of 0.220 (p = 0.002). In contrast, work facilities demonstrated the smallest total effect on performance (0.142; p = 0.006). These findings indicate that leadership quality and employee competency levels exert stronger influences on performance compared to structural factors such as facilities. As conclusion, employee performance is primarily determined by leadership quality and competency development, with work motivation playing a supportive role, while work facilities have a comparatively limited influence. A performance determinant framework grounded in motivation and organizational dynamics provides a robust foundation for designing hospital performance improvement policies.Keywords: hospital management; employee; competency development; leadership style; work motivation; performance